Fenomena Marriage is Scary dalam Konten TikTok terhadap Persepsi Generasi Z tentang Pernikahan - Nazla Aulia; Dessy Safitri; Sujarwo (SYARIAH : Jurnal Ilmu Hukum, 2025)
Marriage is one of the commands in the Quran, in marriage itself it is expected that the husband and wife have a SAMAWA (Sakinah Mawadah Warohmah) relationship, but with the rise of content that appears on TikTok, namely about Marriage is Scary which is related to the personal experiences of the general public about real life in marriage, as well as conflicts that often occur in marriage which can lead to divorce. This can change the way each individual views marriage.